Performativitas Gender Crossplay: Membangun Persona Bishoujo Pada Male to Female (M2F) Crossplayer - Muhlisian, Asep Achmad (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2024)
This study discusses crossplay efforts in building the Bishoujo persona in M2F crossplayer as a form of fluid crossplay gender performativity referring to Judith Butler's theory. This research is a quasi-ethnographic research in Bandung which involves 3 research subjects taken using perposive sampling technique. Data were collected through field observations, social media and in-depth interviews. The results shows that the bishoujo persona was built by emphasizing the similarities with the characters shown in the crossplay. In the process of performing the persona, the three respondents tried their best to match their character through costumes and make-up. The beautiful bishoujo female persona which is more sexy and erotic clearly shown by two respondents. Besides that, it is not only sexy and beautiful, but the female fighter persona or female fighter character with sharper eyes and the ability to use a sword also appears in the bishoujo persona. While one respondent described the bishoujo persona as being more cheerful, with rounder eyes and a loving nature. This is in accordance with Butler's statement that gender identity appears to be seen as something fluid that can move and change in different contexts and times.